Agile Management system role in achieving the development and creativity of employees in Industrial companies in Jordan: A field study on workers in industrial companies - Jordan 2023 - Alrawajfa, Musab Abdullah Ali; Al-Sarayrah, Safaa Mahmoud Bashir (Journal of Economic, Administrative and Legal Sciences, 2024)
This research aims to identify the role of Agile Management in achieving development and creativity among employees of industrial companies in Jordan, where the problem of the study lies in identifying and identifying the most important challenges faced by owners of small and medium-sized companies in Jordan when applying the principles of agile manufacturing. The study community consists of all the companies that applied the agile manufacturing system in Jordan, where the researcher used the descriptive analytical approach. As for the study sample, the comprehensive survey method was used due to the small study community, which consists of 9 industrial companies, where two data collection tools were used, namely: interview and questionnaire, the questionnaire was distributed to all members of the study sample, the questionnaire consisted of 25 paragraphs Data, obtaining and analyzing results. To processes and then use the statistical analysis program. One of the most important findings of the research focused on the most important challenges of applying agile manufacturing in Nineteen out of 25 challenges, the weakness of labor resources with efficiency and resistance to change from employees, poor training, lack of knowledge about agile manufacturing and the absence of the idea of creativity and innovation among workers are the five most important challenges for the application of agile manufacturing. The most important goal measured was to reduce the percentage of errors by about 40 to 60 %. During the research, many recommendations emerged, the most important of which was to adopt a culture of investment in workers, managers and company owners should adopt agile manufacturing systems in their facilities, and they should adopt sound scientific foundations for management, production processes and strategic planning.
Keywords: management; development and creativity; industrial companies; agile management